Radiation Imaging System using a Compact Gamma-ray Imager mounted on a Remotely Operated Machine. Issue 1 (July 2017) - Sato, Yuki; Kawabata, Kuniaki; Ozawa, Shingo; Izumi, Ryo; Kaburagi, Masaaki; Tanifuji, Yuta; Terasaka, Yuta; Miyamura, Hiroko Nakamura; Kawamura, Takuma; Suzuki, Toshikazu; Torii, Tatsuo
Abstract: The development of remote and quick radiation imaging methods for high dose-rate environments is important to accelerate decommissioning of the Fukushima Daiichi Nuclear Power Station (FDNPS). We have developed a remote radiation imaging system consisting of a Compton camera and a multicopter-type drone to remotely measure the distribution of radioactive contaminations inside FDNPS. In outdoor performance evaluation tests in the coastal areas of Fukushima, Japan, the drone system succeeded in observing several hotspots from the sky. In addition, we are developing technology for simultaneous localization and mapping of remotely operated machines such as drones to complete the remote radiation imaging system, which can fly autonomously.